Common beans Tanzania: Climate change risks and opportunities - Demissie, Teferi Dejene; Groot, Annemarie; Duku, Confidence; Budding-Polo, Monserrat; Kabuka, Godfrey; Nkenja, Emanuel; Ninga, Kasian; Lyimo, Raymond; Recha, John W.M.; Osumba, Joab J.L.; Schonenberg, Pierre (2019)
In Tanzania, 7% of the land under production is used for the cultivation of beans. The average yield of beans (dry) is 888 kilograms per hectare (CIAT & World Bank, 2017). Common beans, despite its relatively low profitability, is considered a key value chain crop because of its inclusiveness, nutritional value, food security contribution and cash-crop importance (60% of the produced volumes are commercialized in the local market), and nitrogen fixation.